2022
DOI: 10.1146/annurev-chembioeng-092220-030853
|View full text |Cite
|
Sign up to set email alerts
|

Nanotherapeutics and the Brain

Abstract: Brain disease remains a significant health, social, and economic burden with a high failure rate of translation of therapeutics to the clinic. Nanotherapeutics have represented a promising area of technology investment to improve drug bioavailability and delivery to the brain, with several successes for nanotherapeutic use for central nervous system disease that are currently in the clinic. However, renewed and continued research on the treatment of neurological disorders is critically needed. We explore the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 132 publications
(134 reference statements)
0
4
0
Order By: Relevance
“…A variety of obstacles for NP-based drug delivery have been elegantly described in several recent reviews (Terstappen et al, 2021;Joseph and Nance, 2022;Nance et al, 2022). Among the most problematic of these include immunogenicity, formation of a protein corona on the NP surface, engulfment of NPs by macrophages in the periphery and microglia in the brain, limited endosomal escape, and toxicity (Saraiva et al, 2016).…”
Section: Overcoming Major Hurdles In Np-based Brain Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of obstacles for NP-based drug delivery have been elegantly described in several recent reviews (Terstappen et al, 2021;Joseph and Nance, 2022;Nance et al, 2022). Among the most problematic of these include immunogenicity, formation of a protein corona on the NP surface, engulfment of NPs by macrophages in the periphery and microglia in the brain, limited endosomal escape, and toxicity (Saraiva et al, 2016).…”
Section: Overcoming Major Hurdles In Np-based Brain Drug Deliverymentioning
confidence: 99%
“…10.3389/fncel.2023.1226630 10. Future perspectives As described in several recent and comprehensive reviews (Charabati et al, 2020;Joseph and Nance, 2022;Parrasia et al, 2022), many different types of NP formulations have been reported to increase brain drug delivery. Despite these claims, a viable clinical approach has yet to emerge.…”
Section: Direct Translocation Of Cpps Across the Plasma Membranementioning
confidence: 99%
“…Nano-therapeutics: Nanotherapeutics represent a promising area of CNS drug delivery approaches and have revolutionized the concept of drug delivery across brain barriers with some successful exemplars currently in the clinic [216][217][218]. Nanoparticles (NPs)-based platforms of various size ranges and designs can overcome intact or impaired brain barriers and facilitate efficient CNS drug delivery leveraging transport via multiple mechanisms, including paracellular pathway, cell-mediated transport, adsorptive-mediated transcytosis, RMT, CMT or ligand-receptor interactions [219,220].…”
Section: Transport Mechanisms Studies and (Targeted)drug Deliverymentioning
confidence: 99%
“…Our findings demonstrate that these PLE materials not only mimic the rheological properties of soft tissues but also generate biologically relevant transport. As such, we expect that PLEs can be used as in vitro models of biological tissues to identify physical mechanisms underlying the performance of targeted drug delivery vectors7,8,102 and nanotherapeutics [103][104][105]. Specifically, PLE materials can provide a well-controlled synthetic environment in which we can assess the role of interparticle interactions, transient binding, particle shape, and composition of interstitial fluid on the ability of nanoparticles, liposomes, and other species to penetrate and accumulate within soft tissues.…”
mentioning
confidence: 99%